Effects of zoledronic acid and ibandronic acid on renal functions and calcium, phosphorus and alkaline phosphatase levels in breast cancer patients with bone metastases: a retrospective analysis - Fidan, Evren; Yildiz, Bulent; Kavgaci, Halil; Ozdemir, Feyyaz; Aydin, Fazil (Contemporary Oncology/Współczesna Onkologia, 2012)
Aim of the study : Bone is a common site of metastasis in patients with breast cancer. Skeletal complications associated with bone metastasis are commonly treated with bisphosphonates. However, there are a number of side-effects associated with these, such as renal failure, hypocalcemia and osteonecrosis of the jaw. We aimed to determine the effects of ibandronic and zoledronic acid on serum creatinine (SCr), calcium (Ca), phosphorus (P), alkaline phosphatase (ALP) and estimated glomerular filtration rates (eGFR). The objective was to determine the safety of these bisphosphonates, especially zoledronic acid. Material and methods : Forty-one patients diagnosed with breast cancer (all with bone metastasis) were enrolled. We retrospectively evaluated bisphosphonate type, duration of treatment, infusion time and the parameters SCr, Ca, P, ALP and eGFR. Results : Nineteen patients were included in the zoledronic acid group and 22 in the ibandronic acid group. Mean age in the ibandronic acid group was 53.27 ±11.01, and 53.26 ±9.98 in the zoledro-nic acid group. Median duration of administration in the ibandronic acid group was 11 (7-37) months, and 10 (7-57) months in the zoledronic acid group. SCr levels did not change signi-ficantly during the study period. Pre- and post-treatment Ca levels were also unchanged, but serum ALP levels in the ibandronic acid group and P levels in the zoledronic acid decreased after the final administration; eGFR was unchanged by the end of the study. Conclusions : Zoledronic and ibandronic acid are safe modalities in the treatment of skeletal events in breast cancer patients with bone metastasis.